2020
DOI: 10.15219/em86.1480
|View full text |Cite
|
Sign up to set email alerts
|

Social aspects of introducing online learning - the students' perspective

Abstract: The article presents the introduction of online learning at universities in Poland, which was a solution aimed at preventing, countering and combating COVID-19. Attention was drawn to the perception of this change by the stakeholders, i.e. students. The analysis examines students’ concerns regarding the implementation of this form of learning in selected areas related to access to technology, the organization of classes, and the participation in them, social interactions and administrative activities. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…4 In the majority of cases, this transfer was done without a proper preparation and/or even providing just a limited support for educators and students. 5 The use of digital Learning Management Systems (LMS) has recently turned into a necessity, transforming educational institutions and the habits of educators and students. Students have suddenly had to force themselves to take responsibility for their own learning although they get together with the educators through online platforms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In the majority of cases, this transfer was done without a proper preparation and/or even providing just a limited support for educators and students. 5 The use of digital Learning Management Systems (LMS) has recently turned into a necessity, transforming educational institutions and the habits of educators and students. Students have suddenly had to force themselves to take responsibility for their own learning although they get together with the educators through online platforms.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Moreover, research conducted on a sample of 200 students in Poland showed that students in particular were concerned that online learning would affect class-related issues, such as too much material for self-study, insufficient time to write final papers, or disruption of the course of exams. 5 Another study showed that perceived usefulness, computer self-efficacy and previous experience have a significant positive influence on students’ attitude toward e-learning. 22 A study by Mishra et al 23 at a university in India proved that although online learning during the pandemic was a new experience for students and they felt stressed, they appreciated the initiative taken by the university administration regarding online counselling services for their well-being.…”
Section: Introductionmentioning
confidence: 99%
“…People who were unhappy were doing so because of the fears of pandemics as well as personal transformations (Data.europe.eu. 2020; Pokhrel and Chhetri, 2020;Lis et al in 2020).…”
Section: Introductionmentioning
confidence: 99%